Estimation of technical condition of engines GTD-350 with completed calendar inter- repair resource - Дмитриев, С. А.; Чумак, О. И.; Губань, С. Г. (Proceedings of National Aviation University (archive), 1999)
Considered is the problem of aviation gas-turbine engine GTD-350 with incomplete inter- repair resource but with complete calendar inter-repair resource. Given is the estimation'of economic losses because of underpoduction of the resources and proposed are the ways of solution of this problem